Colonization, cadavers, and color: Considering decolonization of anatomy curricula. Issue 4 (5th January 2022) - Finn, Gabrielle M.; Danquah, Adam; Matthan, Joanna
Abstract: Anatomy is a discipline that, despite its universal nature, offers limited diversity in terms of representation in cadavers, imagery, technology, and models used within teaching. The universal move toward inclusive curricula has put anatomy education under the microscope, particularly with respect to efforts to decolonize curricula. This paper considers the challenges and opportunities to diversify the anatomy curriculum. Decolonizing anatomy education curricula will entail addressing the ingrained cultures within the disciplines, such that produces a number of challenges including: underrepresentation of certain bodies, difficulty talking about difference, and the hidden curriculum in anatomy education. In order to aid educators in achieving inclusive anatomy curricula, a toolkit and considerations are presented, alongside both do's, don'ts and case examples. We highlight the black‐or‐white dichotomy, and the absence of brown in between. The paper is a conversation starter for what it means to begin the process of decolonizing the curriculum within anatomy education.